Palaeoseismicity in the Koteshwor area of the Kathmandu Valley, Nepal, inferred from the soft sediment deformational structures - Gajurel, A. P.; Huyghe, P.; Upreti, B. N.; Mugnier, J. L. (Journal of Nepal Geological Society, 2000)
Palaeoseisms have left their imprints within the Plio-Pleistocene tluvio-lacustrine soft sediments of the Kathmandu Basin. Recently, a temple foundation excavation at Koteshwor exposed a soft sediment layer with deformation al structures. The deformed horizon ranges in thickness from 60 to 90 cm. It can be separated into the following three zones, from top to bottom, respectively: (1) homogenised zone. (2) ball-and-pillow zone, and (3) basal zone. The shaking forces strongly agitated the topmost soft-sediment layer, and in this process, the sediments wcre mixed-up, producing subsequently the homogenised zone. At Koteshwor, the homogenised zone ranges in thickness from 15 to 20 cm. It is associated in a few places with micro-debris containing carbonised wood fragments. In the ball-and-pillow zone, the ball-and-pillow structures are 35-79 cm long and 11- 35 cm high. The laminae of the ball-and-pillow structures are strongly folded or disrupted and recumbent folds are locally observed. The central parts of the ball-and-pillow structures are mostly homogenised and 2-3 cm long wood fragments are accumulated in a few places at the bottom of these structures. In the basal zone (up to 55 cm thick), sediments are upraised and plastically deformed. A marker layer in the basal zone attests to the simultaneity of compression and extension deformational structures, a combination of structures that excludes the slope failure origin for the soft sediment deformation and that is clearly related to ground shaking during an earthquake. The fluvio-lacustrine sediments of the Kathmandu Basin consist of a thin alternation of weakly consolidated and cohesionless silty and sandy layers exhibiting rather good sorting. These conditions and physical properties make them suitable for hydroplastic deformation, liquefaction, and/or tluidisation. Previous studies showed that earthquake-induced liquefaction and fluidisation deformational structures are connected with seismics hocks of M>5. The soft sediment deformational structures with a thickness varying between 60 and 90 cm in a lacustrine environment are formed in seismic intensity zones greater than IX. It is therefore interred that the palaeoseism intensity at Koteshwor was larger than the intensities of the 1833 and 1934 historical earthquakes affecting the Kathmandu Basin.